DETECTION OF TUBERCULOUS MYCOBACTERIA IN SPUTUM AND INTENSITY OF BACILLARY EXCRETION IN TUBERCULOSIS PATIENTS WITH VARIOUS HIV STATUS - V. N. Ziminа; O. E. Mikovа; T. A. Vаretskаya; S. Yu. Degtyarevа; V. I. Sergevnin (Туберкулез и болезни лёгких)
Goal of the study: to investigate the informativeness of tuberculous mycobacteria detection by various techniques and to analyze the intensity of bacillary excretion in tuberculosis patients depending on their HIV status.Materials and methods. 360 HIV patients were examined due to suspected tuberculosis. The diagnostic procedure included two consecutive sputum test for acid fast bacilli (AFB)/tuberculous mycobacteria by fluorescent microscopy, molecular genetic tests and culture on liquid and solid media. Tuberculosis was diagnosed in 178 (49.4%) patients. The comparison group included 354 tuberculosis patients with negative HIV status including 113 patients who underwent the same diagnostic procedure as those suffering from TB/HIV co-infection.Results of the study. AFB were more often detected by fluorescent microscopy in HIV negative tuberculosis patients compared to those with TB/HIV co-infection (32.8 and 24.2% respectively), and the sensitivity of the other testing methods did not differ. Scarce bacillary excretion was confidently more often registered in those suffering from TB/HIV co-infection and less frequently they had massive bacillary excretion detected by culture on solid media compared to HIV negative tuberculosis patients. The complete diagnostic procedure demonstrated better sensitivity in those with TB/HIV co-infection compared to tuberculosis patients with negative HIV status (87.1 and 71.2%).